1988
DOI: 10.1177/106002808802201215
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Prescription Medication in a Pediatric Population

Abstract: This retrospective study describes the prescription medication profile in an outpatient pediatric population (n =510) retrieved from a hospital pharmacy computer file. The survey covers a three-month period. The study population included 281 male and 229 female patients divided according to age into three groups: infant (age 0-12 months); children (age 1-12 years); and adolescents (age 13-18 years). Medications prescribed were classified according to their pharmacotherapeutic properties as described in the Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…the proportion of children who received prescriptions, provide detailed information about the extent of medically treated diseases in childhood. This is important as a supplement to information about prescription rates and each drug as a percentage of all drugs, which most other studies use as the measures of drug use (5,(8)(9)(10)(11). The use of prescription databases is valid in estimating disease prevalence (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the proportion of children who received prescriptions, provide detailed information about the extent of medically treated diseases in childhood. This is important as a supplement to information about prescription rates and each drug as a percentage of all drugs, which most other studies use as the measures of drug use (5,(8)(9)(10)(11). The use of prescription databases is valid in estimating disease prevalence (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Drug utilization studies in children may be used to identify the major therapeutic problems in the population. With few exceptions (4), the existing studies on general drug use were conducted more than a decade ago and were usually based on wholesale statistics or investigations of small populations during a limited period (5)(6)(7)(8)(9)(10)(11). Our study uses population-based individual drug statistics, which allows estimation of the proportion of drug users and the amount of drugs used by the individual.…”
mentioning
confidence: 99%
“…According to a survey of almost 7000 mothers in the UK, 84% of infants received paracetamol during the first 6 mo of life [2]. It is one of the most commonly prescribed drugs by physicians, even in young infants [3]. Millions of children use the drug, and cases of toxicity are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The extent and nature of unlicensed and off-label drug prescription in paediatric clinical care has been the subject of several surveys in Europe [1][2][3][4][5][6][7] and these consistently showed that a very large proportion of prescribed drugs are either unlicensed for use in children or used outside the terms of the product license ("off-label"). Several studies also provide information on the extent of this type of drug prescription in children with respiratory diseases, but information provided is often limited.Respiratory drugs are used for several of the most common paediatric diseases such as asthma, upper and lower respiratory tract infections, rhinitis and sinusitis; conditions that are treated in general practice rather than in clinical care [8][9][10][11][12]. Previous research by the present group revealed that 70% of available respiratory drugs in the Netherlands are not fully licensed for use in children, and many of these (80%) are registered only for specific age/weight groups [13].…”
mentioning
confidence: 99%
“…Respiratory drugs are used for several of the most common paediatric diseases such as asthma, upper and lower respiratory tract infections, rhinitis and sinusitis; conditions that are treated in general practice rather than in clinical care [8][9][10][11][12]. Previous research by the present group revealed that 70% of available respiratory drugs in the Netherlands are not fully licensed for use in children, and many of these (80%) are registered only for specific age/weight groups [13].…”
mentioning
confidence: 99%